Effect of NaCl on papain activity with molecular dynamics simulation - HU Xiao, HUANG Yechuan, GUAN Sitong, DAI Wen, HAN Jiayu, LI Diandian (Zhongguo niangzao)
In order to study the effect of different NaCl concentrations on papain activity and its molecular mechanism, the changes in the activity and structure of papain were analyzed by molecular dynamics simulation and fluorescence spectroscopy based on enzyme activity experiment. The results showed that without NaCl as control, the 3 NaCl concentration treatment groups (0.25 mol/L, 0.50 mol/L, 0.75 mol/L) could inhibit papain activity compared with the control group, and the activity decreased by 13.86%, 23.94% and 31.73%, respectively. The results of molecular simulation showed that the root mean square deviation (RMSD) of the superposition protease skeleton atomic coordinates was relatively stable and had little fluctuation in the whole simulation process. The root mean square fluctuation (RMSF) of protein residue distance in the two high concentration groups was slightly higher than that in the control group. When NaCl 0.75 mol/L was applied, the circumflex radius of the enzyme was relatively maximum, which was 1.684 nm. The number of interprotein hydrogen bonds in 0.75 mol/L group was 2 less than that in control group. With the increase of NaCl concentration, the hydrophobic surface area of protease first increased and then decreased. The proportion of α-helix decreased significantly in the high concentration group. In the control group, the binding between the zymoprotein and the substrate was more uniform and tight than that of 0.75 mol/L group. Therefore, the decrease of papain activity after NaCl treatment in the range of 0.25 to 0.75 mol/L might be related to the enzyme structure changes under this condition, such as the destruction of hydrogen bond, residue fluctuation, and the change of secondary structure such as α-helix.